Construction material selection criteria for timber gridshell application: a literature review - Esmail Adnan Hashem Al-Tameemi,; Mohd Khairul Azhar Mat Sulaiman,; Sudharshan N Raman, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Timber gridshells have the potential to be a sustainable and cost-effective solution for long-span applications and free-form architecture. Despite this, their overall use has been limited, and there is a lack of research focusing on their construction materials. This literature review aims to investigate timber gridshells and their construction materials to identify the criteria used in selecting suitable materials for gridshell applications. A review of peer-reviewed scientific articles, books, and theses was conducted to gather information on timber gridshells, construction materials used in gridshells, timber used in active bending structures, and building standards. The research findings identified six main factors that are important when selecting a suitable material for timber gridshell application: structural strength and strength grading, bending strength and behaviour, bending strength/bending elasticity ratio, durability, commercial availability, and cost. These findings are also discussed to identify the characteristics that make a material suitable for timber gridshell applications, depending on the gridshell’s context, whether in a tropical or international context. This review serves as a necessary reference for architects and engineers when selecting materials for their timber gridshell projects, providing insight into the selection criteria for construction materials and sharing information on the material properties of suitable timber gridshell materials.